Pengaruh Suhu dan Waktu Kempa Terhadap Sifat Fisik dan Mekanik Papan Komposit dari Serat Tkks Berperekat Gambir Berlapis Anyaman Bambu - Junaidi - - (Jurnal Ilmiah Poli Rekayasa, 2018)
Fiber from oil palm empty fruit bunches (OPEFB) can be used as a raw material for the production of composite board.  Gambier can be used in a natural adhesive because of its high tannin content.  Appropriate material to veneer the board and the correct temperature and pressing time are needed to improve the quality of this composite board. This research was to discover the optimal temperature, needed to make woven bamboo veneer composite board from OPEFB fiber and  gambier based adhesive that can fulfill the Indonesian National Standards for veneered composite boards and the pressing time required for the board to reach thermal equilibrium. Results showed that both temperature and pressing time have a significant influence on density, moisture content, thickness swelling and modulus of rupture (MOR) of the boards but not on the internal bond strength or the compression strength parallel to the grain.  Multi-layered composite board pressed at 1300C has weaker physical and mechanical properties than that pressed at  1450C, or 1600C.  Twenty-five minutes of pressing time yielded a better product than 15 minutes and the combination of 25 minutes and 1450C proved to be optimal for the curing of the gambier based adhesive used with 8.4% moisture content fibers. Use of woven bamboo veneer resulted in boards that reached the density, moisture content, thickness swelling at 24 hours (PT24) and MOR National standards SNI 03-2105-2006 for standard veneered particle board however it failed to reach the standard for modulus of elasticity (MOE). The bonding strength of the boards reached the Nation Standard SNI 01-5008.7-1999 of 3.5 kg/cm2 minimum for structural veneered boards.